Immune-Mediated Cerebellar Ataxia Associated With Neuronal Surface Antibodies - Jia, Yu; Li, Mingyu; Li, Dawei; Zhang, Mengyao; Wang, Huifang; Jiao, Lidong; Huang, Zhaoyang; Ye, Jing; Liu, Aihua; Wang, Yuping (Frontiers in Immunology, 2022)
Background Immune-mediated cerebellar ataxias (IMCAs) are common in paraneoplastic cerebellar degeneration (PCD) but rarely occur in patients with neuronal surface antibodies (NSAbs). Although cerebellar ataxias (CAs) associated with anti-NMDAR and anti-CASPR2 have been reported in a few cases, they have never been studied systematically. This study aimed to analyze the characteristics of anti-NSAbs-associated CAs. Methods A retrospective investigation was conducted to identify patients using the keywords IMCAs and NSAbs. We collected the clinical data of 14 patients diagnosed with anti-NSAbs-associated CAs. Results The median age was 33 years (16-66), and the male-to-female ratio was 4:3. Nine were positive for NMDAR-Ab, two for LGI1-Ab, two for CASPR2-Ab, and one for AMPA2R-Ab. CAs were initial symptoms in three patients, and presented during the first two months of the disease course (10 days on average) among the rest of the patients. After the immunotherapy, two cases were free from symptoms, and eight cases recovered satisfactorily (10/14, 71.4%). Compared with other causes of IMCAs, anti-NSAbs were more frequently associated with additional extra-cerebellar symptoms (85.7%), mostly seizures (78.6%) and mental abnormalities (64.3%). In the CSF analysis, pleocytosis was detected in ten patients (71.4%) and oligoclonal bands (OB) were observed in nine patients (64.3%). Moreover, compared with PCD and anti-GAD65-Ab-associated CAs, anti-NSAbs-associated CAs showed a better response to immunotherapy. Conclusion IMCAs are rare and atypical in autoimmune encephalitis with neuronal surface antibodies. Compared with other forms of IMCAs, more symptoms of encephalopathy, a higher rate of pleocytosis and positive OB in CSF, and positive therapeutic effect were the key features of anti-NSAbs-associated CAs.